Analysis of Mathematics Content Knowledge of Mathematics Teachers Based on Bloom's Taxonomy Revision - Nur Inayah; Muchyidin, Arif; Toheri, Toheri (PT Ilmu Inovasi Nusantara, 2024)
This study aims to assess mathematics teachers' understanding of Mathematics Content Knowledge based on the Revised Bloom Taxonomy. The method used is quantitative descriptive research with a survey approach. The respondents of this study were mathematics teachers who taught at SMP/MTs in Losari District, Brebes Regency. Data was collected using non-test instruments in the form of questionnaires and question tests. Data analysis involves presenting data, testing differences, and concluding. The results showed that teachers' understanding of Mathematics Content Knowledge in teaching and mastery of the material was categorized as strong. Based on Bloom's revised taxonomy, teachers have good mastery, especially in knowledge dimensions such as factual, conceptual, procedural, and metacognitive knowledge, which are categorized as high. There was no significant difference in the average Mathematics Content Knowledge score of teachers, either with a working period of less than 10 years, 10-15 years, or more than 15 years.